Metaphorical representation of the phenomenon of knowledgein the phraseology of the Russian and English languages: productivity of macrometaphors - Gutovskaya, Marina S.; Shaibakova, Darya V. (Journal of the Belarusian State University. Philology, 2024)
The article presents the results of a comparative analysis of the ways of metaphorical organisation of the ideas about the phenomenon of knowledge in Russian and English phraseology with an emphasis on the productivity of macrometaphors. The study implements a cognitive approach to metaphor, which assumes that metaphorical units reflect thought mechanisms and they serve as a tool for associating abstract concepts with more specific ones. The corpus of Russian and English phraseological units with the semantics of ‘знание’/‘knowledge’ is formed with a two-stage contrastive lexicographic technique and systematised considering the classification of macrometaphors proposed by J. Lakoff and M. Johnson and supplemented by A. P. Chudinov, which distinguishes ontological, orientational, anthropomorphic, sociomorphic, naturomorphic, and artefact macrometaphors. Macrometaphors as the most generalised metaphorical constructions, concretised by groups of conceptual metaphors, are considered from the perspective of their productivity in the figurative organisation of the phenomenon of knowledge. The article establishes the similarities and distinctiveness in the metaphorical representation of knowledge in the phraseology of two languages. The obtained results could be used in further research in the field of cognitive phraseology, development of the theory of cognitive metaphor, comparative linguocultural study of phraseology.
Keywords: phraseological unit; phraseology with the semantics of knowledge; macrometaphor; productivity of macrometaphors; conceptual metaphor